Membedah Demokrasi: Tantangan, Implikasi terhadap kualitas, dan harapan untuk masa depan - St. Hadijah Wahid; -, Nurul Amelia; Misra Miranda; Ashari; Agustina; Asriani Lestari; Ari Sandi (LANCAH: Jurnal Inovasi dan Tren, 2025)
This article discusses challenges and expectations for Indonesian democracy, with an emphasis on several issues that affect the quality of the democratic system. The main characteristics that are identified include corruption, social and economic determinants, human rights violations, radicalism, the use of kebebasan berpendapat, political pragmatism, and a lack of access to information. As a result of these tantangan-tantangan, the political environment is not healthy, with oligarchy and economic politics limiting public participation and akuntabilitas. Despite this, there is a need to improve through increased transparency and accountability, independence for the peradilan, legal and political reform, and political education for the next generation. Human rights protection and sipil kebebasan also serve as a foundation for encouraging public participation in political processes. This article highlights the importance of cooperation between the government, the Sipil populace, and various other relevant parties in order to create a more robust and inclusive democracy in Indonesia.